Portugal as a culinary tourism destination: Determinants of revisit and recommendation - Heriana, Wienda (2022)
Portugal is a country with many Michelin-starred restaurants and produces many award-wining wines. With the rich gastronomical aspects that Portugal has, it is worth determining the factors that influence people to revisit and recommend Portugal as a culinary tourism destination. This study is using quantitative method. A questionnaire was filled out by people who have been to Portugal or are currently in Portugal and travel around the country to experience the cuisine. A total of 314 responses were obtained. Data was analysed using descriptive statistics and hypothesis tests, namely the independent t-test. To test the hypotheses model relationships, correlation analyses were conducted. Results show that domestic and international tourists mostly experience food tourism differently and respondents typically agree with all the items. All of the hypotheses are verified except the relationship between neophilia and novelty. The study revealed that local food tourism experience has relationships with local food culture, authenticity, prestige, and social interaction. Likewise, satisfaction positively impacts tourists’ intention to revisit and recommend.